Reeder and Felson’s Gamuts in Radiology Comprehensive Lists of Roentgen Differential Diagnosis - Reeder, Maurice M. (Springer New York, 1993)
by Elias G. Theros, M. D. I. Meschan Distinguished Professor of Radiology, Wake Forest University Medical Center, Winston-Salem, North Carolina, USA Amongst the present generation of radiologists, beguiled by the glamour and excitement of the new high tech imaging and interventional modalities, too few have developed a strong sense of differential diagnosis based on radiologic pattern recognition and its correlation with clinical and laboratory fmdings. There is no question about the incredible contribution by the new modalities to our diagnostic armamentarium, but in the evolution of mod em-day radiologic practice, the cognitive element has been neglected and our abilities as diagnosticians have suffered. The advent of this third edition of Reeder and Felson's Gamuts in Radiology is timely and welcome. As always, use of the gamut lists will help evoke differential thinking, and this has been enhanced by the addition of over 250 new gamuts as well as by the updating of over three-fourths of the existing gamuts. Interestingly, about 130 of the new gamuts are MRI Gamuts developed by Dr. William Bradley whose enormous experience in clinical MRI has prepared him to think differentially about look-a-like patterns and/or locations of lesions displayed by this modality. This is an important step forward in the use of this remarkable new diagnostic tool